Polyphenol Phase‐II Metabolites are Detectable in Human Plasma after Ingestion of 13C Labeled Spinach—a Pilot Intervention Trial in Young Healthy Adults. Issue 10 (20th April 2018) - Passon, Maike; Bühlmeier, Judith; Zimmermann, Benno F.; Stratmann, Anja; Latz, Stefan; Stehle, Peter; Galensa, Rudolf
Abstract : Scope: After intrinsic labeling of spinach ( Spinacia oleracea L., Chenopodiaceae) with 13 CO2, we investigated if labeled polyphenol metabolites were detectable in human plasma. Methods and result: In a pilot intervention trial, five healthy men consumed 5 g freeze‐dried 13 C labeled spinach, including a total amount of 160 μmol methoxyflavonols, including 70 μmol 5, 3′, 4′‐trihydroxy‐3‐methoxy‐6, 7‐methylendioxyflavone‐4′‐glucuronide. Plasma samples of all subjects were analyzed with regard to their 13 C/ 12 C ratio. Additionally, 13 C labeled metabolites of patuletin, spinacetin, and 5, 3′, 4′‐trihydroxy‐3‐methoxy‐6, 7‐methylendioxyflavone (TMM) were analyzed in plasma samples in a subgroup of three subjects. TMM‐glucuronide, TMM‐sulfate, and spinacetin‐glucuronide‐sulfate, the latter as 12 C1 13 C16 and 13 C17 isotopologs, were tentatively identified. Plasma concentration of TMM‐glucuronide and TMM‐sulfate reached cmax from 19.1–54.3 and 22.5–125.5 nmol L –1, respectively, 7–9 h post‐ingestion. Conclusion: It seems likely that 13 C labeled TMM‐glucuronide and TMM‐sulfate are phase‐II metabolites which were converted after colonic transformation. Variations in plasma kinetics were observed for these two metabolites and may be attributed to the individual composition of the microbiota. We conclude that 13 C labeled polyphenol metabolites are detectable and quantifiable in human plasma. Abstract : For 13 C‐TMM‐4′‐ 13 C‐glucuronide, a major polyphenol in intrinsically labeled spinach, deglucuronidation and reglucuronidation as well as sulfation reactions are observed during human metabolism. 13 C‐TMM‐ 12 C‐glucuronide, 13 C‐TMM‐sulfate, and spinacetin‐glucuronide‐sulfate, the spinacetin as 12 C1 13 C16 and 13 C17 isotopologs, are detected in human plasma 7–9 h post‐ingestion. cmax of 13 C‐TMM‐ 12 C‐glucuronide and 13 C‐TMM‐sulfate range from 19.1–54.3 and 22.5–125.5 nmol L –1, respectively.